Systematics of Phasia Latreille (Diptera: Tachinidae) - Sun, Xuekui; Marshall, Stephen A. (Zootaxa, 2003)
The genus Phasia (Diptera, Tachinidae) is redefined and the world species (excluding Neotropical species) are revised. Six species-groups are defined, and seventy-five species are described or redescribed, including 31 new species. Revised host lists and distribution maps are given. Fifteen generic names are treated as new synonyms of Phasia: Akosempomyia Villeneuve, Alophorophasia Townsend, Androeuryops Beneway, Besserioides Curran, Bogosiella Villeneuve, Campbellia Miller, Efftayloria Malloch, Epaulophasia Townsend, Heyneophasia Townsend, Kosempomyia Villeneuve, Paraphasiana Townsend, Tayloria Malloch, Trichophasia Townsend, Xanthotrichius Townsend and Xiphophasia Townsend. The following new species are described: Phasia africana, P. australiensis, P. brachyptera, P. cana, P. clavigralla, P. bifurca, P. cylindrata, P. distincta, P. faceta, P. frontata, P. furcata, P. japanensis, P. kuodi, P. lauta, P. malaisei, P. malayana, P. mathisi, P. minima, P. nirgromaculata, P. rotundata, P. serrata, P. siberica, P. sichuanensis, P. singuliseta, P. subnitida, P. sumatrana, P. transvaalensis, P. triangulata, P. wangi, P. woodi and P. yunnanica. The following new synonyms are proposed: P. umbrifera (Wulp), P. occidentalis (Brooks), P. opaca (Coquillett), P. polita (Brooks), P. alaskensis (Brooks) and P. umbrosa (Wulp) are junior synonyms of P. aeneoventris (Williston); P. nigra (Brooks) is a junior synonym of P. albipennis (Brooks); P. karczewskii (Draber-Mo½ko) is a junior synonym of P. aldrichii (Townsend); P. splendida (Coquillett) and P. meliceris (Reinhard) are junior synonyms of P. aurulans Meigen; P. cockaynei (Miller) and P. lancifer (Malloch) are junior synonyms of P. campbelli (Miller); P. peruviana (Townsend), P. pollinosa (Brooks), P. auricaudata (Brooks) and P. dimidiata (Townsend) are junior synonyms of P. chilensis (Macquart); P. basalis (Malloch), P. hyalis (Malloch) and P. nigrihirta (Malloch) are junior synonyms of P. lepidofera (Malloch); P. bancrofti (Paramonov) is a junior synonym of P. normalis (Curran); P. celer (Townsend) and P. argentifrons (Brooks) are junior synonyms of P. purpurascens (Townsend); P. fumosa (Coquillett), P. nitida (Coquillett), P. phasioides (Coquillett), P. pulverea (Coquillett), P. furva West and P. brevineura West are junior synonyms of P. robertsonii (Townsend); P. chrysis (Malloch), P. aureiventris (Curran), P. costalis (Malloch), P. nigrisquama (Malloch) and P. discalis (Malloch) are junior synonyms of P. rufiventris (Macquart); P. lativentris (Malloch) is a junior synonym of P. sensua (Curran). A cladistic analysis of Phasia, based on fifty-one characters, is presented and the zoogeography of the genus is discussed.